A secondary spherical lithium-rich manganese-based positive electrode material and its preparation method and application

By preparing a secondary spherical lithium-rich manganese-based positive electrode material with an O2-type crystal structure, the problems of cycle stability and mechanical failure in lithium-ion batteries are solved, and efficient electrochemical performance and structural stability are achieved, which is suitable for large-scale production.

CN119481030BActive Publication Date: 2025-10-03CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411617926.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-10-03
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Existing lithium-rich manganese-based positive electrode materials have problems such as poor cycling stability, mechanical failure and poor electrochemical performance in lithium-ion batteries, especially it is difficult to maintain structural integrity and electrochemical performance in large-scale applications.

Method used

A preparation method for secondary spherical lithium-rich manganese-based positive electrode materials is adopted. By mixing the nickel-manganese co-precipitation precursor with the lithium source, calcining and low-temperature ion exchange method, thick and long plate-like primary particles and spherical secondary particles with O2-type crystal structure are prepared, avoiding the introduction of impurities by high-temperature sintering and maintaining the structural integrity of the material.

Benefits of technology

It improves the mechanical stability and electrochemical properties of the material, reduces irreversible capacity loss, prolongs the cycle life, makes it suitable for large-scale production, and reduces process costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481030B_ABST
    Figure CN119481030B_ABST
Patent Text Reader

Abstract

The present invention discloses a secondary spherical lithium-rich manganese-based positive electrode material, a preparation method and application thereof. The method of the present invention adopts an ion exchange method to prepare a secondary spherical lithium-rich manganese-based positive electrode material with primary particles in the shape of thick plates. This method alleviates the structural and performance attenuation problems of the lithium-rich manganese-based positive electrode material by synergistically utilizing the secondary particle design and lattice design scheme. The test results of the product show that the secondary spherical lithium-rich manganese-based positive electrode material with primary particles in the shape of thick plates prepared by the present invention has a small specific surface area and high mechanical stability, which helps to improve the energy density and cycle stability of the material and reduce the problem of voltage attenuation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a secondary spherical lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries, as the most indispensable components, play a vital role in various portable electronic devices, electric vehicles and large-scale energy storage. However, traditional cathode materials have been unable to meet the demand for high specific energy in modern society. Nowadays, lithium-rich layered oxides have become one of the important choices for next-generation cathode materials, with high energy density reaching 1000Wh kg. -1 .

[0003] In lithium-rich manganese-based polycrystalline materials, due to the presence of a large number of grain boundaries, this will lead to the formation of intergranular cracks during the repeated insertion and extraction of lithium, increase the exposure of the electrochemically active surface, thereby promoting the occurrence of side reactions and accelerating structural degradation. Compared with polycrystalline, lithium-rich manganese-based single crystal materials have higher crystallinity and fewer grain boundaries, which help to improve mechanical stability and reduce surface defects, thereby maintaining good structural integrity during long-term cycles. However, in larger single crystal particles, due to the long diffusion distance, the lithium ion concentration distribution inside the grains is uneven, affecting the performance of gram capacity and cycle stability. In addition, its preparation process is relatively complicated, which to a certain extent limits its large-scale application.

[0004] Lithium-rich manganese-based O2 and O3 structures are two distinct crystal arrangements with significant differences in material properties and electrochemical behavior. In the O2 structure, the Li-O octahedron and the Mn-O octahedron are connected by face-sharing. This arrangement effectively hinders transition metal migration, improves structural stability, avoids irreversible lattice oxygen release and structural degradation, and reduces phase transitions caused by transition metal migration.

[0005] Chinese patent CN117996067 discloses an O2-type lithium-rich manganese-based positive electrode material and its preparation and application. A P2-type sodium precursor is first sintered, and then the O2 structure is obtained by the Li / Na exchange method. The design of alkali metal and oxygen double vacancies reduces the loss of lattice oxygen and oxygen release in the positive electrode material, so that the voltage decay is effectively alleviated. However, the Li / Na exchange method it adopts is carried out in a molten salt state. Since molten salt is highly corrosive to many materials, sintering in containers such as crucibles is prone to corrosion and introduces impurities, thereby affecting the material properties. Experiments have shown that the molten salt method will destroy its morphology and generally cannot maintain the structure of secondary spherical particles. Therefore, this solution cannot solve the mechanical failure of secondary particles during the cycle, and the electrochemical performance is still not enough to meet the requirements of large-scale applications. Summary of the Invention

[0006] One of the purposes of the present invention is to provide a secondary spherical lithium-rich manganese-based positive electrode material, which can improve the cycle stability and voltage decay problems of lithium-ion batteries as a lithium-ion battery material, and solve the problem of mechanical failure of secondary particles during circulation.

[0007] A second object of the present invention is to provide a method for preparing the secondary spherical lithium-rich manganese-based positive electrode material.

[0008] The third object of the present invention is to provide an application of the secondary spherical lithium-rich manganese-based positive electrode material.

[0009] The present invention provides a secondary spherical lithium-rich manganese-based positive electrode material, wherein the primary particles of the secondary spherical lithium-rich manganese-based positive electrode material are in the form of thick and long plates and are aggregated into secondary spherical particles, and have an O2 type crystal structure; the chemical formula of the secondary spherical lithium-rich manganese-based positive electrode material is Li(Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0010] The present invention provides a method for preparing the secondary spherical lithium-rich manganese-based positive electrode material, comprising the following steps:

[0011] S1. A nickel-manganese co-precipitated precursor, a sodium source, and a lithium source are mixed and ground into a powder according to a preset ratio, and then calcined to obtain a P2 phase sodium precursor;

[0012] S2. Add the P2 phase sodium precursor obtained in step S1 to an organic solvent, then add excess lithium salt, heat treat, wash and dry to obtain the secondary spherical lithium-rich manganese-based positive electrode material.

[0013] Furthermore, in step S1, the nickel-manganese co-precipitation precursor is prepared by using sodium tartrate as a complexing agent and a solution of sodium hydroxide and sodium pyrophosphate mixed in proportion as a precipitant; the nickel-manganese co-precipitation precursor has a primary particle morphology of thick and long strips, and agglomerated into spherical secondary particles, and D50 = 4 to 15 μm, and a tap density of 1.6 to 1.8 g / cm 3 , with a specific surface area of ​​15 to 25 m 2 / g; the sodium source includes sodium carbonate, sodium oxalate, sodium hydroxide, sodium bicarbonate and sodium acetate; the lithium source includes lithium carbonate, lithium hydroxide, lithium chloride, lithium phosphate and lithium acetate.

[0014] Furthermore, the chemical formula of the P2 phase sodium precursor obtained in step S1 is Na 5 / 6 (Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0015] Furthermore, in step S1, the calcination process conditions are: calcining at a calcination temperature of 400-600°C for 4-7 hours in an oxygen or air atmosphere, and then calcining at a calcination temperature of 900-1000°C for 8-12 hours; the heating rate at the beginning of calcination is 1-5°C / min.

[0016] Different calcination conditions will affect the phase purity of the product P2 phase sodium precursor. The calcination temperature conditions in the method provided by the present invention can prepare a pure P2 phase sodium precursor.

[0017] Furthermore, in step S2, the organic solvent is ethanol; and the lithium salt is lithium bromide.

[0018] Furthermore, in step S2, the process conditions of the heat treatment are: heating in a water bath at 50-100° C. for 12-24 hours.

[0019] The method of the present invention uses heat treatment to promote a gentle exchange of lithium ions in the organic solvent with sodium ions in the sodium precursor of the P2 phase, which is less likely to introduce impurities and produces a stable O2 material. Furthermore, compared to ion exchange methods using molten salts, the method of the present invention can maintain the secondary spherical structure of the primary particles in the product material, which is a thick, elongated plate.

[0020] Furthermore, in step S2, the powder after the heat treatment is washed 3 to 4 times with deionized water by suction filtration or centrifugation, and then dried at 50 to 150° C. for 24 to 48 hours.

[0021] After ion exchange, deionized water is used to wash and dry multiple times in order to wash away excess lithium and sodium ions.

[0022] The present invention also provides an application of the secondary spherical lithium-rich manganese-based positive electrode material.

[0023] Furthermore, the application of the secondary spherical lithium-rich manganese-based positive electrode material is specifically to use the secondary spherical lithium-rich manganese-based positive electrode material to prepare a lithium-ion battery.

[0024] Furthermore, a method for preparing a lithium-ion battery using a secondary spherical lithium-rich manganese-based positive electrode material specifically comprises the following steps:

[0025] The secondary spherical lithium-rich manganese-based positive electrode material, a conductive agent, and a binder are mixed and dissolved in an appropriate amount of solvent, the slurry is evenly applied on the surface of the current collector, and vacuum dried to obtain a lithium-ion battery positive electrode sheet;

[0026] The positive electrode sheet, separator, electrolyte and negative electrode sheet of the lithium-ion battery are assembled in a glove box filled with argon gas, and the lithium-ion battery is obtained after pressing and standing.

[0027] Specifically, the mass ratio of the secondary spherical lithium-rich manganese-based positive electrode material, the conductive agent, and the binder when mixed is 8:1:1; the current collector is aluminum foil; the conductive agent is carbon black; the binder is PVDF; the solvent is N-methylpyrrolidone; the diaphragm is a commercial polypropylene diaphragm; the electrolyte is a commercial electrolyte; and the negative electrode is a lithium sheet.

[0028] Beneficial effects of the present invention:

[0029] (1) The secondary spherical lithium-rich manganese-based positive electrode material proposed in the present invention has a special morphology in which the primary particles are thick and long strips. Such larger primary particles have higher crystallinity and fewer grain boundaries, which helps to improve mechanical stability and reduce surface defects, thereby maintaining better structural integrity in long-term cycles. At the same time, such large primary particles and agglomerated secondary spherical particles help to improve the tap density and compaction density of the lithium-rich manganese-based material, and increase the energy density of the material. The spherical material has excellent fluidity and dispersibility, and can be more evenly dispersed when preparing the electrode slurry, which helps to improve the consistency and electrochemical performance of the battery pole piece. This feature is particularly suitable for large-scale production, which can effectively reduce process costs and improve production efficiency;

[0030] (2) The present invention proposes a method for preparing a secondary spherical lithium-rich manganese-based positive electrode material with thick plate-like primary particles. The material has an O2 structure. Compared with the lithium-rich manganese-based material with an O3 structure, the O2-type lithium-rich manganese-based positive electrode material can hinder the migration of transition metals and effectively hinder the redox of anionic oxygen, thereby reducing the capacity provided by the irreversible redox reaction in the first cycle, reducing the loss of lattice oxygen and oxygen release. The improvement in lattice oxygen stability during the cycle reduces the degree of structural degradation, and the lithium-rich layered oxide positive electrode material exhibits better cycle stability and slower voltage decay. In addition, the improvement in lattice oxygen stability also improves the thermal stability of the material.

[0031] (3) The method for preparing a secondary spherical lithium-rich manganese-based positive electrode material with thick plate-shaped primary particles proposed in the present invention adopts an ion exchange method. The ion exchange process only requires low-temperature heating at 50°C-100°C, which effectively solves the problems of severe Li / Ni mixing and large-scale volatilization of lithium salts caused by high-temperature sintering. Compared with the ion exchange performed in the molten salt state, this method promotes the gentle exchange of lithium ions dissolved in the organic solvent with sodium ions in the P2 phase sodium precursor at low temperature. This method is not easy to introduce impurities and can better maintain the secondary spherical structure with thick plate-shaped primary particles;

[0032] (4) The lithium-ion battery prepared by the positive electrode material of the present invention exhibits excellent electrochemical performance. At a high cut-off voltage of 2.0-4.8V, the first discharge capacity can reach 200-250mAhg -1, the irreversible capacity decreased to 39.03 mAh g -1 The average working voltage decayed by only 97 mV after 200 cycles at a 1C rate, and the capacity retention rate was no less than 87%. Furthermore, no obvious cracks were observed in the particles of the electrode after cycling in the electron microscope image. The method of the present invention is convenient and simple and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is an SEM image of the secondary spherical lithium-rich manganese-based positive electrode material obtained in Example 1;

[0034] Figure 2 This is the XRD pattern of the sodium precursor material obtained in Example 1;

[0035] Figure 3 This is the XRD pattern of the secondary spherical lithium-rich manganese-based positive electrode material obtained in Example 1;

[0036] Figure 4 This is an SEM image of the electrode sheet of the secondary spherical lithium-rich manganese-based positive electrode material obtained in Example 1 after cycling 200 cycles at a current density of 1C;

[0037] Figure 5 This is an SEM image of the electrode sheet of the conventional lithium-rich manganese-based positive electrode material obtained in Comparative Example 1 after cycling 200 cycles at a current density of 1C;

[0038] Figure 6 The first cycle charge and discharge curve of the battery prepared with the secondary spherical lithium-rich manganese-based positive electrode material obtained in Example 1 at a current density of 0.1C;

[0039] Figure 7 This is the SEM image of the conventional lithium-rich manganese-based positive electrode material obtained in Comparative Example 4. DETAILED DESCRIPTION

[0040] The present invention will be further described in detail below with reference to specific embodiments, but the protection scope of the present invention is not limited to the contents described above.

[0041] Example 1

[0042] Nickel sulfate and manganese sulfate were dissolved in deionized water to prepare a 1.6 mol / L salt solution with a nickel-manganese molar ratio of 1:3. 1.4 g / L sodium tartrate was added to the salt solution as a complexing agent. A 6 mol / L mixed solution of sodium hydroxide and sodium pyrophosphate was prepared as a precipitant at a molar ratio of 25:1. The salt solution was introduced into a reactor containing a nitrogen atmosphere at a flow rate of 1.5 L / h and the precipitant at a flow rate of 0.6 L / h. The sodium tartrate complexing agent in the bottom liquid was 1.4 g / L. The temperature was 40°C to 50°C, the pH was 11.6, and the rotation speed was 750 rpm. When the particle size reached 7 μm, the feed was stopped. After aging for 10 hours, the mixture was centrifuged and dried to obtain a primary particle morphology of thick and long strips with a D50 of 4 to 15 μm and a tap density of 1.6 to 1.8 g / cm. 3 , with a specific surface area of ​​15 to 25 m 2 / g of nickel-manganese co-precipitation precursor.

[0043] The prepared nickel-manganese coprecipitation precursor, sodium carbonate and lithium carbonate were mixed and ground into powder in proportion. The mixed powder contained Na:Li:Ni:Mn=5 / 6:0.2:0.2:0.6. In order to adjust the volatility of lithium and sodium at high temperature, an excess of 5% lithium source and sodium source was added. The obtained powder was transferred to a tube furnace and heated at a rate of 3°C / min in an oxygen atmosphere, kept at a calcination temperature of 500°C for 5 hours, and kept at a calcination temperature of 950°C for 10 hours. The temperature was naturally cooled to room temperature to obtain the P2 phase sodium precursor: Na 5 / 6 (Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0044] The P2 phase sodium precursor powder was added to a 10-fold excess of 5M lithium bromide ethanol solution and heated at 80°C for 24 hours to obtain the O2 phase material. It was washed with deionized water 4 times and then dried in an oven at 80°C for 24 hours to remove excess water to obtain a secondary spherical lithium-rich manganese-based cathode material Li(Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0045] The obtained secondary spherical lithium-rich manganese-based cathode material was scanned by scanning electron microscope, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the primary particles of the secondary spherical lithium-rich manganese-based positive electrode material are in the shape of thick long strips and have relatively clear grain boundaries, and the secondary particles are spherical.

[0046] The obtained P2 phase sodium precursor was subjected to X-ray powder diffraction test to determine the phase, and the test results were Figure 2 shown.

[0047] The obtained secondary spherical lithium-rich manganese-based cathode material was subjected to X-ray powder diffraction test to determine the phase, and the test results were Figure 3 As shown, the diffraction peaks of the obtained positive electrode material are completely consistent with the peaks of the O2 phase of the P63mc space group in the PDF card.

[0048] The resulting secondary spherical lithium-rich manganese-based cathode material was weighed and mixed with carbon black and PVDF in the following amounts: 0.6g of secondary spherical lithium-rich manganese-based cathode material, 0.075g of carbon black, and 0.075g of PVDF. 1.875g of N-methylpyrrolidone (NMP) was then added, stirred evenly, and coated on aluminum foil to a thickness of 18µm. The mixture was then dried in a vacuum oven at 120°C for 24 hours to obtain a lithium battery cathode.

[0049] The lithium battery positive electrode sheet and the metal negative electrode, commercial polypropylene separator, and commercial electrolyte were assembled into CR2025 button cells in a glove box filled with argon and with water and oxygen below 0.01 ppm.

[0050] The obtained CR2025 button battery was tested for battery performance. The constant current charge and discharge curve performance test was carried out in the test voltage range of 2.0 to 4.8 V. The first cycle charge and discharge curve at 0.1C was as follows: Figure 6 As shown, the first cycle coulombic efficiency is 85.7% and the first discharge capacity reaches 235mAhg -1 , and the capacity retention rate can reach 88.8% after 200 cycles at a current density of 1C, and the average working voltage before and after the cycle only decays by 97mV.

[0051] The positive electrode of the battery after 200 cycles was scanned by scanning electron microscope, and the results are as follows: Figure 4 As shown, there are no obvious cracks in the positive electrode particles.

[0052] Example 2

[0053] Nickel sulfate and manganese sulfate were dissolved in deionized water to prepare a 1.6 mol / L salt solution with a nickel-manganese molar ratio of 1:3. 1.4 g / L sodium tartrate was added to the salt solution as a complexing agent. A 6 mol / L mixed solution of sodium hydroxide and sodium pyrophosphate was prepared as a precipitant at a molar ratio of 25:1. The salt solution was introduced into a reactor containing a nitrogen atmosphere at a flow rate of 1.5 L / h and the precipitant at a flow rate of 0.6 L / h. The sodium tartrate complexing agent in the bottom liquid was 1.4 g / L. The temperature was 40°C to 50°C, the pH was 11.6, and the rotation speed was 750 rpm. When the particle size reached 7 μm, the feed was stopped. After aging for 10 hours, the mixture was centrifuged and dried to obtain a primary particle morphology of thick and long strips with a D50 of 4 to 15 μm and a tap density of 1.6 to 1.8 g / cm. 3 , with a specific surface area of ​​15 to 25 m 2 / g of nickel-manganese co-precipitation precursor.

[0054] The prepared nickel-manganese coprecipitation precursor, sodium carbonate and lithium carbonate were mixed and ground into powder in proportion. The mixed powder contained Na:Li:Ni:Mn=5 / 6:0.2:0.2:0.6. In order to adjust the volatility of lithium and sodium at high temperature, an excess of 5% lithium source and sodium source was added. The obtained powder was transferred to a tube furnace and heated at a rate of 3°C / min in an oxygen atmosphere, kept at a calcination temperature of 500°C for 5 hours, and kept at a calcination temperature of 900°C for 10 hours. It naturally cooled to room temperature to obtain the P2 phase sodium precursor: Na 5 / 6 (Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0055] The P2 phase sodium precursor powder was added to a 10-fold excess of 5M lithium bromide ethanol solution and heated at 100°C for 24 hours to obtain the O2 phase material. It was washed with deionized water 4 times and then dried in an oven at 80°C for 24 hours to remove excess water to obtain a secondary spherical lithium-rich manganese-based cathode material Li(Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0056] The resulting secondary spherical lithium-rich manganese-based cathode material was weighed and mixed with carbon black and PVDF in the following amounts: 0.6g of secondary spherical lithium-rich manganese-based cathode material, 0.075g of carbon black, and 0.075g of PVDF. 1.875g of N-methylpyrrolidone (NMP) was then added, stirred evenly, and coated on aluminum foil to a thickness of 18µm. The mixture was then dried in a vacuum oven at 120°C for 24 hours to obtain a lithium battery cathode.

[0057] The lithium battery positive electrode sheet and the metal negative electrode, commercial polypropylene separator, and commercial electrolyte were assembled into CR2025 button cells in a glove box filled with argon and with water and oxygen below 0.01 ppm.

[0058] The obtained CR2025 button battery was tested for battery performance. The constant current charge and discharge curve performance test was carried out in the test voltage range of 2.0 to 4.8 V. The first discharge capacity reached 228 mAh g -1 , and the capacity retention rate can reach 86.7% after 200 cycles at a current density of 1C, and the average working voltage before and after the cycle only decays by 108mV.

[0059] Comparative Example 1

[0060] Take the conventional nickel-manganese co-precipitation precursor and lithium carbonate and grind them into powder in proportion to ensure that Li:Ni:Mn=1.2:0.2:0.6. In order to adjust the volatility of lithium at high temperature, an excess of 5% lithium source is added. The obtained powder is transferred to a tube furnace and heated at a temperature of 500℃ for 5 hours and at a temperature of 800℃ for 10 hours under an oxygen atmosphere at a heating rate of 3℃ / min. It is naturally cooled to room temperature to obtain the conventional lithium-rich manganese-based positive electrode material: Li(Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0061] After testing, the conventional lithium-rich manganese-based positive electrode material obtained was an O3 structure, and the primary particle morphology was coarse and short granular.

[0062] The obtained conventional lithium-rich manganese-based cathode material was mixed with carbon black and PVDF in the following amounts: 0.6g of conventional lithium-rich manganese-based cathode material, 0.075g of carbon black, and 0.075g of PVDF. 1.875g of N-methylpyrrolidone (NMP) was then added, stirred evenly, and coated on aluminum foil to a thickness of 18µm. The mixture was then dried in a vacuum oven at 120°C for 24 hours to obtain a lithium battery cathode.

[0063] The lithium battery positive electrode sheet and the metal negative electrode, commercial polypropylene separator, and commercial electrolyte were assembled into CR2025 button cells in a glove box filled with argon and with water and oxygen below 0.01 ppm.

[0064] The prepared lithium-ion battery was subjected to constant current charge and discharge curve performance test in the test voltage range of 2.0-4.8V. The first cycle coulomb efficiency at 0.1C was 78%, and the first discharge capacity was 203mAhg -1 , and the capacity retention rate after 200 cycles at a current density of 1C is 71.7%, and the average working voltage before and after the cycle decays by 303mV.

[0065] The positive electrode sheet after 200 cycles was scanned by scanning electron microscope. Figure 5 As shown, it can be seen that obvious cracks appear on the cathode particles of the target cathode material after 200 cycles.

[0066] Comparative Example 2

[0067] Nickel sulfate and manganese sulfate were dissolved in deionized water to prepare a 1.6 mol / L salt solution with a nickel-manganese molar ratio of 1:3. 1.4 g / L sodium tartrate was added to the salt solution as a complexing agent. A 6 mol / L mixed solution of sodium hydroxide and sodium pyrophosphate was prepared as a precipitant at a molar ratio of 25:1. The salt solution was introduced into a reactor containing a nitrogen atmosphere at a flow rate of 1.5 L / h and the precipitant at a flow rate of 0.6 L / h. The sodium tartrate complexing agent in the bottom liquid was 1.4 g / L. The temperature was 40°C to 50°C, the pH was 11.6, and the rotation speed was 750 rpm. When the particle size reached 7 μm, the feed was stopped. After aging for 10 hours, the mixture was centrifuged and dried to obtain a primary particle morphology of thick and long strips with a D50 of 4 to 15 μm and a tap density of 1.6 to 1.8 g / cm. 3 , with a specific surface area of ​​15 to 25 m 2 / g of nickel-manganese co-precipitation precursor.

[0068] The prepared nickel-manganese coprecipitation precursor and lithium carbonate were mixed and ground into powder in proportion to ensure that Li:Ni:Mn=1.2:0.2:0.6. In order to adjust the volatility of lithium at high temperature, an excess of 5% lithium source was added. The obtained powder was transferred to a tube furnace and heated at a temperature of 500℃ for 5 hours and at a temperature of 950℃ for 10 hours under an oxygen atmosphere at a heating rate of 3℃ / min. The temperature naturally cooled to room temperature to obtain a conventional lithium-rich manganese-based positive electrode material: Li(Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0069] After testing, the conventional lithium-rich manganese-based positive electrode material obtained was an O3 structure, and the primary particle morphology was long and plate-like.

[0070] The obtained conventional lithium-rich manganese-based cathode material was mixed with carbon black and PVDF in the following amounts: 0.6g of conventional lithium-rich manganese-based cathode material, 0.075g of carbon black, and 0.075g of PVDF. 1.875g of N-methylpyrrolidone (NMP) was then added, stirred evenly, and coated on aluminum foil to a thickness of 18µm. The mixture was then dried in a vacuum oven at 120°C for 24 hours to obtain a lithium battery cathode.

[0071] The lithium battery positive electrode sheet and the metal negative electrode, commercial polypropylene separator, and commercial electrolyte were assembled into CR2025 button cells in a glove box filled with argon and with water and oxygen below 0.01 ppm.

[0072] The prepared lithium-ion battery was subjected to constant current charge and discharge curve performance test in the test voltage range of 2.0-4.8V. The initial discharge capacity was 215mAhg -1, and the capacity retention rate after 200 cycles at a current density of 1C is 77.6%, and the average working voltage before and after the cycle decays by 272mV.

[0073] Comparative Example 3

[0074] Take the conventional nickel-manganese co-precipitation precursor, sodium carbonate, and lithium carbonate and grind them into powder in proportion. The mixed powder contains Na:Li:Ni:Mn=5 / 6:0.2:0.2:0.6. In order to adjust the volatility of lithium and sodium at high temperature, an excess of 5% lithium source and sodium source is added. The obtained powder is transferred to a tube furnace and heated at a heating rate of 3°C / min in an oxygen atmosphere, and kept at a calcination temperature of 500°C for 5 hours and at a calcination temperature of 800°C for 10 hours. It is naturally cooled to room temperature to obtain the P2 phase sodium precursor: Na 5 / 6 (Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0075] The P2 phase sodium precursor powder was added to a 10-fold excess of 5M lithium bromide ethanol solution and heated at 80°C for 24 hours to obtain the O2 phase material. It was washed with deionized water 4 times and then dried in an oven at 80°C for 24 hours to remove excess water to obtain a secondary spherical lithium-rich manganese-based cathode material Li(Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0076] After testing, the conventional lithium-rich manganese-based positive electrode material obtained was an O2 structure, and the primary particle morphology was coarse and short granular.

[0077] The obtained conventional lithium-rich manganese-based cathode material was mixed with carbon black and PVDF in the following amounts: 0.6g of conventional lithium-rich manganese-based cathode material, 0.075g of carbon black, and 0.075g of PVDF. 1.875g of N-methylpyrrolidone (NMP) was then added, stirred evenly, and coated on aluminum foil to a thickness of 18µm. The mixture was then dried in a vacuum oven at 120°C for 24 hours to obtain a lithium battery cathode.

[0078] The lithium battery positive electrode sheet and the metal negative electrode, commercial polypropylene separator, and commercial electrolyte were assembled into CR2025 button cells in a glove box filled with argon and with water and oxygen below 0.01 ppm.

[0079] The prepared lithium-ion battery was subjected to constant current charge and discharge curve performance test in the test voltage range of 2.0-4.8V. The initial discharge capacity was 208mAhg -1 , and the capacity retention rate after 200 cycles at a current density of 1C is 73.2%, and the average working voltage before and after the cycle decays by 167mV.

[0080] Comparative Example 4

[0081] Nickel sulfate and manganese sulfate were dissolved in deionized water to prepare a 1.6 mol / L salt solution with a nickel-manganese molar ratio of 1:3. 1.4 g / L sodium tartrate was added to the salt solution as a complexing agent. A 6 mol / L mixed solution of sodium hydroxide and sodium pyrophosphate was prepared as a precipitant at a molar ratio of 25:1. The salt solution was introduced into a reactor containing a nitrogen atmosphere at a flow rate of 1.5 L / h and the precipitant at a flow rate of 0.6 L / h. The sodium tartrate complexing agent in the bottom liquid was 1.4 g / L. The temperature was 40°C to 50°C, the pH was 11.6, and the rotation speed was 750 rpm. When the particle size reached 7 μm, the feed was stopped. After aging for 10 hours, the mixture was centrifuged and dried to obtain a primary particle morphology of thick and long strips with a D50 of 4 to 15 μm and a tap density of 1.6 to 1.8 g / cm. 3 , with a specific surface area of ​​15 to 25 m 2 / g of nickel-manganese co-precipitation precursor.

[0082] The prepared nickel-manganese coprecipitation precursor, sodium carbonate and lithium carbonate were mixed and ground into powder in proportion. The mixed powder contained Na:Li:Ni:Mn=5 / 6:0.2:0.2:0.6. In order to adjust the volatility of lithium and sodium at high temperature, an excess of 5% lithium source and sodium source was added. The obtained powder was transferred to a tube furnace and heated at a rate of 3°C / min in an oxygen atmosphere, kept at a calcination temperature of 500°C for 5 hours, and kept at a calcination temperature of 950°C for 10 hours. The temperature was naturally cooled to room temperature to obtain the P2 phase sodium precursor: Na 5 / 6 (Li 0.2 Ni 0.2 Mn 0.6 )O2.

[0083] 2 g of the above-obtained P2 phase sodium precursor, 13.8 g of lithium nitrate, and 2.1 g of lithium chloride were ground evenly in a mortar. The resulting mixture was placed in a porcelain boat and heated to 300°C at a heating rate of 3°C / min under an argon atmosphere and kept warm for 4 hours. After cooling to room temperature, it was washed and filtered 5 times with deionized water, and then dried in an oven at 80°C for 24 hours to remove excess moisture to obtain an O2-structured lithium-rich manganese-based positive electrode material.

[0084] The conventional lithium-rich manganese-based cathode material was scanned by scanning electron microscopy, and the results were as follows: Figure 7 shown.

[0085] After testing, the conventional lithium-rich manganese-based positive electrode material obtained was an O2 structure, and the primary particle morphology was coarse and short granular.

[0086] The resulting lithium-rich manganese-based cathode material was mixed with carbon black and PVDF in the following amounts: 0.6g of lithium-rich manganese-based cathode material, 0.075g of carbon black, and 0.075g of PVDF. 1.875g of N-methylpyrrolidone (NMP) was then added, stirred evenly, and coated on aluminum foil to a thickness of 18µm. The mixture was then dried in a vacuum oven at 120°C for 24 hours to obtain a lithium battery cathode.

[0087] The lithium battery positive electrode sheet and the metal negative electrode, commercial polypropylene separator, and commercial electrolyte were assembled into CR2025 button cells in a glove box filled with argon and with water and oxygen below 0.01 ppm.

[0088] The prepared lithium-ion battery was subjected to constant current charge and discharge curve performance test in the test voltage range of 2.0-4.8V. The initial discharge capacity was 227mAhg -1 , and the capacity retention rate after 200 cycles at a current density of 1C is 71.1%, and the average working voltage before and after the cycle decays by 107mV.

Claims

1. A method for preparing a secondary spherical lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: S1 using nickel-manganese co-precipitation precursor, sodium source, lithium source, according to a preset ratio of mixed ground into powder, and then calcined to obtain a P2 phase sodium precursor; S2. The sodium precursor P2 phase obtained in step S1 is added to an organic solvent, and then an excess of lithium salt is added, heated, washed and dried to obtain the secondary spherical lithium-rich manganese-based cathode material; The primary particles of the secondary spherical lithium-rich manganese-based positive electrode material are thick and long plate-shaped, with D50 = 4~15um and a tap density of 1.6~1.8g / cm 3 , with a specific surface area of ​​15~25m 2 / g, and agglomerated into secondary spherical particles, and having an O2 type crystal structure; the chemical formula of the secondary spherical lithium-rich manganese-based positive electrode material is Li(Li 0.2 Ni 0.2 Mn 0.6 )O2; In step S1, the chemical formula of the obtained P2 phase sodium precursor is Na 5 / 6 (Li 0.2 Ni 0.2 Mn 0.6 )O2; In step S2, the process conditions of the heat treatment are: heating in a water bath at 50-100° C. for 12-24 hours.

2. The method for preparing a secondary spherical lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step S1, the nickel-manganese co-precipitation precursor is prepared using sodium tartrate as a complexing agent and a solution of sodium hydroxide and sodium pyrophosphate mixed in proportion as a precipitant; the sodium source includes sodium carbonate, sodium oxalate, sodium hydroxide, sodium bicarbonate or sodium acetate; the lithium source includes lithium carbonate, lithium hydroxide, lithium chloride, lithium phosphate or lithium acetate.

3. The method for preparing a secondary spherical lithium-rich manganese-based cathode material according to claim 1, characterized in that: In step S1, the calcination process conditions are: calcination at a calcination temperature of 400-600°C for 4-7 hours in an oxygen or air atmosphere, and then calcination at a calcination temperature of 900-1000°C for 8-12 hours; the heating rate at the beginning of calcination is 1-5°C / min.

4. The method for preparing a secondary spherical lithium-rich manganese-based cathode material according to claim 1, characterized in that: In step S2, the organic solvent is ethanol; and the lithium salt is lithium bromide.

5. The method for preparing a secondary spherical lithium-rich manganese-based cathode material according to claim 1, characterized in that: In step S2, the washing and drying are specifically as follows: the powder after the heat treatment is washed 3 to 4 times with deionized water by suction filtration or centrifugation, and then dried at 50 to 150°C for 24 to 48 hours.

6. Application of the secondary spherical lithium-rich manganese-based positive electrode material prepared by the method for preparing the secondary spherical lithium-rich manganese-based positive electrode material according to any one of claims 1 to 5 in lithium-ion batteries.

7. The use according to claim 6, characterized in that The method for preparing a lithium-ion battery using the secondary spherical lithium-rich manganese-based positive electrode material comprises the following steps: The secondary spherical lithium-rich manganese-based positive electrode material, a conductive agent, and a binder are mixed and dissolved in an appropriate amount of solvent, the slurry is evenly applied on the surface of the current collector, and vacuum dried to obtain a lithium-ion battery positive electrode sheet; The positive electrode sheet, separator, electrolyte and negative electrode sheet of the lithium-ion battery are assembled in a glove box filled with argon gas, and the lithium-ion battery is obtained after pressing and standing.

8. The use according to claim 7, characterized in that The mass ratio of the secondary spherical lithium-rich manganese-based positive electrode material, the conductive agent, and the binder when mixed is 8:1:1; the current collector is aluminum foil; the conductive agent is carbon black; the binder is PVDF; the solvent is N-methylpyrrolidone; the separator is a polypropylene separator; and the negative electrode is a lithium sheet.

Citation Information

Patent Citations

  • Lithium ion secondary battery, positive electrode active material, positive electrode, electric tool, electric vehicle, and power storage system

    CN102544572A

  • Preparation and improvement method of lithium-rich positive electrode material for lithium-ion battery

    CN106784677A